Enteropathogenic Escherichia coli Infection in Cancer and Immunosuppressed Patients. (15th September 2020) - Olvera, Adilene; Carter, Hannah; Rajan, Anubama; Carlin, Lily G; Yu, Xiaomin; Zeng, Xi-Lei; Shelburne, Samuel; Bhatti, Micah; Blutt, Sarah E; Shroyer, Noah F; Jenq, Robert; Estes, Mary K; et al.
Abstract: Background: The role of enteropathogenic Escherichia coli (EPEC) as a cause of diarrhea in cancer and immunocompromised patients is controversial. Quantitation of fecal bacterial loads has been proposed as a method to differentiate colonized from truly infected patients. Methods: We studied 77 adult cancer and immunosuppressed patients with diarrhea and EPEC identified in stools by FilmArray, 25 patients with pathogen-negative diarrhea, and 21 healthy adults without diarrhea. Stools were studied by quantitative polymerase chain reaction (qRT-PCR) for EPEC genes eaeA and lifA/efa-1 and strains characterized for virulence factors and adherence to human intestinal enteroids (HIEs). Results: Patients with EPEC were more likely to have community-acquired diarrhea (odds ratio, 3.82 [95% confidence interval, 1.5–10.0]; P = .008) compared with pathogen-negative cases. Although EPEC was identified in 3 of 21 (14%) healthy subjects by qPCR, the bacterial burden was low compared to patients with diarrhea (≤55 vs median, 6 × 10 4 bacteria/mg stool; P < .001). Among EPEC patients, the bacterial burden was higher in those who were immunosuppressed (median, 6.7 × 10 3 vs 55 bacteria/mg; P < .001) and those with fecal lifA/ ifa-1 (median, 5 × 10 4 vs 120 bacteria/mg; P = .015). Response to antimicrobial therapy was seen in 44 of 48 (92%) patients with EPEC as the sole pathogen. Antimicrobial resistance was common and strains exhibited distinct patterns of adherence with variable cytotoxicity when studied in HIEs. Cancer care was delayed in 13% of patients. Conclusions: Immunosuppressed cancer patients with EPEC-associated diarrhea carry high burden of EPEC with strains that are resistant to antibiotics, exhibit novel patterns of adherence when studied in HIEs, and interfere with cancer care. Abstract : Cancer patients with diarrhea shed a larger number of enteropathogenic Escherichia coli (EPEC) than asymptomatic adults, particularly when immunosuppressed, and fecal bacterial load correlated with the presence of lifA/efa-1 . When studied in human intestinal organoids, EPEC demonstrated diverse and novel patterns of adherence.